1988
DOI: 10.1080/09553008814552331
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Human Cellular Radiosensitivity: II. The Survival Following Gamma-irradiation of Unstimulated (G0) T-lymphocytes, T-lymphocyte Lines, Lymphoblastoid Cell Lines and Fibroblasts from Normal Donors, from Ataxia-telangiectasia Patients and from Ataxia-telangiectasia Heterozygotes

Abstract: We have measured clonal survival following gamma-irradiation of unstimulated (G0) T-lymphocytes from 35 donors, of 11 T-lymphocyte cell lines, of six lymphoblastoid cell lines, and of nine primary fibroblast strains for which we have G0 T-lymphocyte material from the same donor. Amongst the G0 lymphocytes we have results from nine normal donors, from eight cord bloods, from seven ataxia-telangiectasia (A-T) patients and from nine A-T heterozygotes. Although there is some variation between samples, G0 T-lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…It seems likely that reduction of the ATM protein even to the extent of 50% as predicted in A-T heterozygotes alters the response to ionizing radiation. While A-T heterozygotes do not exhibit any of the major symptoms of the disease, cells in culture have intermediate radiosensitivity between homozygotes and controls as determined by a series of di erent assays (Chen et al, 1978;Rudolph et al, 1989;Cole et al, 1988;Lavin et al, 1992;Rosin and Ochs, 1986;Sanford and Parshad, 1990;Scott et al, 1994;Shiloh et al, 1986). This intermediate radiosensitivity is most likely due to reduced ATM protein since the great majority of mutations in ATM are predicted to give rise to truncated proteins (Savitsky et al, 1995a;Gilad et al, 1996;Byrd et al, 1996;Telatar et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that reduction of the ATM protein even to the extent of 50% as predicted in A-T heterozygotes alters the response to ionizing radiation. While A-T heterozygotes do not exhibit any of the major symptoms of the disease, cells in culture have intermediate radiosensitivity between homozygotes and controls as determined by a series of di erent assays (Chen et al, 1978;Rudolph et al, 1989;Cole et al, 1988;Lavin et al, 1992;Rosin and Ochs, 1986;Sanford and Parshad, 1990;Scott et al, 1994;Shiloh et al, 1986). This intermediate radiosensitivity is most likely due to reduced ATM protein since the great majority of mutations in ATM are predicted to give rise to truncated proteins (Savitsky et al, 1995a;Gilad et al, 1996;Byrd et al, 1996;Telatar et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Defined disorders with radiosensitive phenotypes, such as the ataxia-telangiectasia (AT) syndrome, show that genetic factors can strongly determine the radiosensitivity of humans (Thacker, 1994). In addition, studies have revealed that cells from AT heterozygotes show increased radiosensitivity (Cole et al, 1988;Weeks et al, 1991;West et al, 1995). There are ongoing efforts to evaluate a possible role of AT heterozygosity for over-reaction to RT, particularly in breast cancer patients (Weeks et al, 1991;West et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1A and B both the ear and kidney cultures exhibited sensitivity to IR, consistent with retention of the Atm phenotype. Despite reports of slight sensitivity to IR for human cells heterozygous for Atm (Cole et al, 1988;Heim et al, 1992), no signi®cant dierence was observed when comparing the ear and kidney Atm heterozygous de®cient cells with the wild type cells. These contrasting observations could be due to the null mutation in the mouse Atm knockout allele as opposed to dominant negative mutations that may be present in some human cells (Meyn, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Virally transformed human lymphocytes and ®bro-blasts from A-T patients are available (Meyn, 1993;Pandita and Hittelman, 1992;Cole et al, 1988;Roscheisen et al, 1994), but the presence of viral oncoproteins can complicate the interpretation of data obtained with these immortalized cell lines. Recently, telomerase expression has been used to extend the life span of human A-T ®broblasts without apparent loss of radiation sensitivity (Wood et al, 2001).…”
Section: Discussionmentioning
confidence: 99%